Influence of integrated nutrient management and spacing on growth and yield of rice (BIRRI dhan69) (Research in Agriculture Livestock and Fisheries, 2020)
With the development of high yielding rice varieties, use of chemical fertilizers increased rapidly in Bangladesh. Depending on chemical fertilizer solely is not wise and maintaining soil health becomes a great concern worldwide. The purpose of the study is to know about the effect of organic and inorganic fertilizer on growth and yield of rice. The experiment was laid out in a split-plot design with four nutrient managements (N1= BRRI recommended fertilizer dose (N-P-K-S-Z = 117-19-58-15-4 kg ha-1), N2= 75% of BRRI recommended dose, N3= 75% of BRRI recommended dose + Decomposed poultry litter (DPL) (2.5 t ha-1) and N4= No fertilizer) in the main plots and three spacing(S1= 20 cm × 20 cm, S2= 20 cm × 15 cm and S3= 25 cm × 15 cm) in the subplots with three replications. In growth and yield characteristics, insignificant difference was found for different spacing but significant difference was found for different nutrient managements. N1 and N3 performed better than N2 and N4 in all observed characteristics. N1 and N3 gave statistically similar result in yield. The result revealed that, with the application of 2.5 t ha-1 DPL we can reduce 25% chemical fertilizer without yield reduction in rice.Res. Agric., Livest. Fish.7(1): 25-32, April 2020